Seasonal Dynamics of Goats’ Infestation with Bovicola Caprae - F. S., Pulotov; A.Sh., Ismoilov; D. M., Boltayev; A. A., Djalolov (American Journal of Biodiversity, 2025)
This article provides detailed information on determining the seasonal degree of infestation of goats with Bovicola caprae in goat farms across the Republic.